2022
DOI: 10.1093/jn/nxac061
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Titanium Dioxide Intake by Diet and Stool Assessment among US Healthy Adults

Abstract: Background Titanium dioxide (TiO2/E171) is used in foods primarily as a whitening agent. Little is known regarding TiO2 exposure in the U.S. Objective To quantify stool TiO2 content among U.S. adults and evaluate its association with estimated intake. Methods Adults participated in phase 1 (three, 24h dietary recalls (DR) and stool TiO2 measured from three ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In order to contextualize these doses, we used the estimated human daily intake (EDI) and their equivalent dose in Caco-2 cell defined by Sohal et al (2020) 28 and Putra et al (2022). 29 We transformed our doses (10 and 100 μg mL −1 ) to the same units (μg cm −2 ) for intestinal cells to obtain equivalent EDIs (Table S1†). Following a similar procedure, we calculated the dose range/surface and the equivalent of EDI for Drosophila melanogaster , using estimated values for food intake 30 and midgut surface.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In order to contextualize these doses, we used the estimated human daily intake (EDI) and their equivalent dose in Caco-2 cell defined by Sohal et al (2020) 28 and Putra et al (2022). 29 We transformed our doses (10 and 100 μg mL −1 ) to the same units (μg cm −2 ) for intestinal cells to obtain equivalent EDIs (Table S1†). Following a similar procedure, we calculated the dose range/surface and the equivalent of EDI for Drosophila melanogaster , using estimated values for food intake 30 and midgut surface.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Global production of TiO 2 NPs was estimated to reach approximately 2.5 million metric tons by 2025 (Ahamed et al, 2020). Analysis of US grocery store data suggested that the dietary intake of TiO 2 could be as high as 5 mg/kg body weight per day from food products (Putra et al, 2022). Moreover, the European Food Safety Authority (EFSA) estimated that the maximum level of exposure to E171, a food‐grade TiO 2 , occurs in children between the ages of 3 to 9, who ingest an average of 1.9 to 11.5 mg/kg body weight per day (Cornu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%